2015
DOI: 10.1007/s11356-015-4147-x
|View full text |Cite
|
Sign up to set email alerts
|

Autotrophic perchlorate reduction kinetics of a microbial consortium using elemental sulfur as an electron donor

Abstract: The perchlorate reduction kinetic parameters of a microbial consortium using elemental sulfur (S(0)) as an electron donor were investigated in batch experiments. Standard Monod substrate utilization and biomass accumulation models were employed to fit the experimental data for microbial perchlorate reduction. The maximum observed yield coefficient for the microbial consortium was 0.19 mg dry weight (DW) mg(-1) ClO4 (-), suggesting that the microbial consortium had a slow growth rate using S(0) as the electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…A total of 23 genera (relative abundance ≥ 1% in at least one sample) were identified in the two communities ( Figure 4A ). Methyloversatilis have been previously reported as denitrification bacteria ( Li et al, 2019 ) and play a dominant role in removal in autotrophic reactors ( Gao et al, 2015 ), accounting for 5.10 and 2.63% of the A1 and A2 communities, respectively. Comparison of the microbial communities of the A1 and A2 communities revealed that the microbial community structures of the membrane surface samples (A1 and A2) differed after RSM optimization.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 23 genera (relative abundance ≥ 1% in at least one sample) were identified in the two communities ( Figure 4A ). Methyloversatilis have been previously reported as denitrification bacteria ( Li et al, 2019 ) and play a dominant role in removal in autotrophic reactors ( Gao et al, 2015 ), accounting for 5.10 and 2.63% of the A1 and A2 communities, respectively. Comparison of the microbial communities of the A1 and A2 communities revealed that the microbial community structures of the membrane surface samples (A1 and A2) differed after RSM optimization.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of processes to remove perchlorate from water have been developed owing to the environmental importance . These include adsorption, biodegradation, chemical reduction, electrochemical reduction, bio‐electrochemical reduction, and photo‐electrocatalytic reduction …”
Section: Introductionmentioning
confidence: 99%
“…Perchlorate is known to be used in the manufacture of solid rocket fuels, propellants, fireworks, explosives, and other commercial products (Achenbach et al 2001;Coates and Achenbach 2004;Gao et al 2015). Recently, perchlorate (ClO 4 − ) contamination of surface water and groundwater has received much attention by researchers and policy makers due to its toxicity, high solubility, and stability in water (Srinivasan and Sorial 2009).…”
Section: Introductionmentioning
confidence: 99%
“…a Effects of molar ratios of perchlorate (100 mg/L) to acetate (100∼750 mg/L) on specific growth rates. b Perchlorate removal according to various initial concentrations of perchlorate (containing 250∼3500 mg/L of acetate satisfying perchlorate to acetate mass concentration ratio of 1:5) reported that some PCRB can utilize H 2(Dudley et al 2008;Shrout et al 2005;Zhang et al 2002), H 2 S(Gregoire et al 2014), elemental sulfur (S 0 ,Gao et al 2015;Ju et al 2007;Ju et al 2008), S 2 O 3 2− (Ju et al 2008), ferrous [Fe(II)] iron…”
mentioning
confidence: 99%